Strategi Pengembangan Pariwisata di Kabupaten Tana Toraja - Rambulangi, Abedneigo C.; Batara, Mince (UKI Toraja Press, 2021)
The tourism potential of Tana Toraja Regency is many potential. The development of this potential is expected to encourage regional development. Currently, there are 7 (seven) tourism development strategies implemented in Tana Toraja. Therefore, it is necessary to evaluate the implementation of 7 (seven) strategies. The purpose of this research to explore the information about the level of influence the progress implementing of seven strategies and factors influence the development of tourism in Tana Toraja Regency. This research is qualitative with descriptive type. The results of this research, are : (1) all strategies have been implemented but the results of the implementation of these strategies are different. Where the strategy of strengthening marketing and product development was successfully implemented and has given significant results. The strategy in distribution and multiplier and product development strategy has a significant results, but there are still parts have not been successfully implemented, and HR development strategy, Spatial development and tourism interest processing strategy have not provided significant results for the development of Tana Toraja tourism. (2) The driving aspects of tourism development owned by Tana Toraja include: The naturalness of tourism objects, the role and participation of the Toraja society and tourism promotion objects are very diverse and creative. (3) And inhibiting aspects are: Inadequate facilities and infrastructure, unprofessional human resources in the field of tourism and the legal basis (Perda) specifically on tourism is not.